双圆弧齿轮齿间、接触迹间载荷分配分析 - 孙大乐; 杨文通; 蔡春源 (Jixie chuandong)
A method of accurately analyzing load distribution of unrunning-in and enough running -in double circular arc gear among the teeth and their contactpatterns has been presented by the coupling of threedimensional elastic contact finite element method withrunning-in simulation method. The regulation oftransverse load distribution of GB12759-91 doublecircular arc gear in an angular pitch has been calculatedby the examples. This method provides the thoriticalbasis on researching the strength, running-in and lubrication properties of double circular arc gear.